Intercultural Sensitivity in Indonesian and Japanese Literary Works is the Development of Literary Learning in the Digital Era - Simanjuntak, Nensy Megawati; Wardhani, Widya Desary Setia; Sumartono, Sumartono; Padmasari, Arumtyas Puspitanig; Tobing, Victor MTL; Kumar, Atul (KIRYOKU, 2025)
Intercultural or another term for intercultural is a concept that brings together two or more cultural elements to then be integrated into new knowledge and understanding for each individual or group of people who want to know about the development of foreign cultures. In learning literature, intercultural is needed as a forum to develop global insight and knowledge. Learning literature is not only learning about the nature and content of literary works, learning literature means learning to be cultured and cultivating the culture itself. The data for this study were taken from famous novels from each country. The research data are: A novel entitled "Geisha" by Arthur Golden from Japan and a novel entitled "Cantik itu Luka" by Eka Kurniawan from Indonesia. This study is a qualitative phenomenological study by raising the similarities in culture and the position of women in the two novels used as data. This study aims to explain that there are similarities in culture in Indonesia and Japan that can be observed through learning literature, especially fictional works in the form of novels. This study found that Japanese women and Indonesian women are considered inferior and only tools to satisfy male lust. But behind that assumption, there is strength and politeness in women that makes them valuable and able to rise against the reality of life presented in front of them. Women are not weak creatures, whatever their culture, women are important entities that support the sustainability of human life on earth.